Neuropathology of organophosphate poisoning in dairy cattle - Yulvian Sani; Indraningsih . (Jurnal Ilmu Ternak dan Veteriner, 2007)
The purpose of this study is to investigate pathological changes in brain tissues of Frisien Holstein dairy cattle affected by organophosphate (OP). The study was directed to anticipate spongiform encephalopathy. Samples consisted of animal feeds, sera and brain tissues were collected from Lembang, West Java.  Animal feeds (fodders and commercial feed) were collected directly from the dairy farms around Lembang. Sera (31 samples) were from dairy cattle owned by the local farmers and brain tissues were from the local animal slaughter house. Pesticide residues were analysed following a standard procedure using gas chromatography (GC). There was an interaction between pesticide residues in animal feeds, residue level of pesticides in sera and brain tissues to cause encephalopathy in dairy cattle. Pesticide contamination in animal feeds was regarded as the source of encephalopathy in dairy cattle. The total average of OP residues (16.8 ppb) were lower than organochlorines/OC (18.7 ppb) in fodder, showing that pesticides were originated from the contaminated soils. On the other hand, the total average of OP residues in commercial feeds (12.0 ppb), sera (85.6 ppb) and brain tissues (22.7 ppb) were higher than OC (1.8; 16.7; and 5.1 ppb). The OP appears more frequently used for dairy farm activity as insecticides. Histopathological examination for brain tissues of dairy cattle showed that most cattle were diagnosed as encephalopathy with microscopic changes of vacuolation, neuronal necrosis, chromatolysis of neurons and nucleolysis of neurons. The encephalopathy was confirmed in rats intoxicated with chlorpyrifos methyl as severe brain damage with spongiform-like lesions. Key Words: Encephalopathy, Organophosphates, Cattle